OP0285 The Pathogenic Role of Immune Complexes Containing Scleroderma-Specific Autoantibodies in the Inductor Phase of the Disease. (9th June 2015) - Chighizola, C.B.; Raschi, E.; Cesana, L.; Borghi, M.O.; Meroni, P.L.
Abstract : Background: Systemic sclerosis (SSc) is a chronic autoimmune condition characterized by tissue fibrosis, microvascular alterations and immune dysfunction with specific autoantibodies.These autoantibodies are highly specific for SSc diagnosis, and provide the most reliable tool to predict disease subset and the pattern of organ involvement. Despite such diagnostic and prognostic role, no evidence supporting the pathogenic potential of these autoantibodies has to date been raised. Objectives: The working hypothesis envisaged that immune complexes (IC) containing scleroderma specific autoantibodies -rather than the mere antibody- might be able to elicit a pro-inflammatory and pro-fibrotic signaling cascade in target cells, thus contributing to SSc etiopathogenesis. Since scleroderma autoantibodies bind –either directly or via bridge proteins- to nucleic acids, it was also postulated that the effects induced by SSc-IC might be mediated by Toll-like Receptors (TLR). Methods: Fibroblasts have been isolated from healthy skin biopsies then cultured in adequate conditions. IC have been purified from sera of SSc patients bearing different autoantibody specificities (antibodies against centromeric proteins, DNA topoisomerase I, RNA polymerase and Th/To) or healthy controls using polyethylen glycol precipitation. Cell cultures have been incubated with pathologic and control IC and TLR3 [Poly(I:C)] and TLR4 (LPS) agonists. Cell activation parameters have been assessed: mRNA levels of TLR3 and TLR9 and type I interferons (IFN-α and IFN-β) have been investigated by real-Time PCR; ICAM-1 expression has been evaluated by cell-ELISA and the secretion of IL-6 and IL-8 in culture supernatants has been measured by commercial ELISA kits. Furthermore, the involvement of intracellular signaling pathways culminating with the activation of p38-MAPK, NFκB and SAPK-JNK has been assessed. Results: Stimulation of normal skin fibroblasts with pathologic IC induced a significant increase in the gene expression levels of both IFN-α and IFN-β; similar results have been reported in the presence of TLR agonists but not control IC. In addition, ICAM-1 expression and IL-6 and IL-8 secretion were up-regulated by Poly(I:C), LPS and scleroderma but not control IC. The expression levels of TLR3 and -to a greater extent- TLR9 were significantly increased upon stimulation with TLR3 agonist and scleroderma but not control IC. Further, pathologic IC induced the activation of p38-MAPK, NFκB and SAPK-JNK. Conclusions: These data provide the first demonstration of the pathogenic role of IC isolated from scleroderma patients with different autoantibody specificities in the inductor phase of SSc. Indeed, pathologic IC can interact with normal skin fibroblasts, inducing a pro-inflammatory phenotype mediated by p38-MAPK, NFκB and SAPK-JNK. These evidences fit well with the diagnostic and prognostic role of scleroderma-specific autoantibodies. Preliminary results on TLR3 and TLR9 mRNA upregulation upon SSc but not control IC stimulation suggest the potential involvement of these innate immunity receptors; future work will be aimed at better characterizing the nature of scleroderma IC interaction with cellular targets. Disclosure of Interest: None declared